PROBLEMATIKA KEPALA MADRASAH DALAM MENGEMBANGKAN MTS NURUL TAQWA MANADO - Sulfa Potiua (Jurnal Inovasi Penelitian, 2021)
This study aims to determine the problems (obstacles and solutions) of madrasah in the development of MTs Nurut Taqwa Manado. This study uses a qualitative approach, namely research that tries to reveal phenomena in social situations in depth based on existing realities. The results showed that the problems (obstacles and solutions) of the madrasah in the development of MTs Nurut Taqwa Manado include: (a) the lack of public awareness to participate in educating children in the madrasah because there are many madrasas that are more advanced and complete with facilities and infrastructure; and (b) the infrastructure at MTs Nurut Taqwa Manando is still very limited so that people are not sure about the quality of education available at the madrasa. The solution for the head of the madrasa in facing various obstacles in developing MTs Nurut Taqwa Manado is to keep trying as much as possible in socializing about the importance of madrasas in forming character or morality for students and continuing to strengthen cooperation with the community and government and trying as much as possible to use facilities and infrastructure which exists.